Analysis Of the Application of Foreign Curriculum for Kindergarten Students - Lee, Anasthasia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
This study aims to assess the application of Pearson curriculum for kindergarten students. Because, instead of using K-2013, international schools in Indonesia have been applying foreign curriculum. The findings of this study revealed Indonesian international school kindergarten students achieved more in terms of acquiring a second language and have more cultural knowledge and understanding. This analysis can be used a source for another schools or teacher to evaluate the curriculum applied in the school.